SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN SUPPLIER MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) - Nugraha, Deny Wiria; -, Wirdayanti (FORISTEK : Forum Teknik Elektro dan Teknologi Informasi, 2013)
Supplier selection is multicriteria problem, since for selecting the supplier who will become partner, decision maker must consider many criteria to measure supplier performance. One of the models that is used to measure supplier performance is Supplier Performance Rating used in Kingston-Warren Corporation. The key aspects related to that model are Quality, Cost and Delivery.Â One of tools that used by decision maker to select supplier is making a computer system that can interact with decision maker. The system is called Decision Support System (DSS) for supplier selection. The process of supplier selection uses Analytical Hierarchy Process (AHP) model. AHP model conduct supplier selection by making paired matrix comparison from defined criterion. Result of AHP model calculation is in the form of priority value, so that the highest priority value produced by the model is used by decision maker to choose the best candidate supplier. Keywords: Decision Support System (DSS), Analytical Hierarchy Process (AHP), Supplier Selection.